Anxious medico with nicotine patch: a case report - K., Jayanthi M.; M., Satish A.; Raj, Ranjith; A., Priyanka C. (International Journal of Basic & Clinical Pharmacology, 2019)
We often suffer more in our imaginations than in reality. Anxiety is a terrible experience, you could even have an attack and no one would even know most of the times because it is an inward thing. People do get anxious and experience this feeling most of the times in life. Up to an extent its normal as much as it can be controlled if not this unpleasant feeling overrules. We learn to combat this feeling as the age passes but it also depends on different environmental, social occupational factors and the level of stress to overcome can be difficult. Many non-pharmacological and pharmacological methods are available to combat anxiety disorder. Self-medications can be occupational hazard and is strongly entrenched within the culture of both physicians and medical students as an accepted way to buffer their work performance. We are reporting a case of an anxious medico self-medicated to combat anxiety.